Haemostatic factors associated with vascular thrombosis in patients with systemic lupus erythematosus and the lupus anticoagulant. - Mayumi, T (1991)
To elucidate the mechanism of vascular thrombosis in patients with systemic lupus erythematosus and the lupus anticoagulant changes in factors associated with haemostasis were investigated. The lupus anticoagulant was associated with an increased incidence of thrombosis, particularly cerebral thrombosis. Concentrations of fibrinopeptide A and fibrinopeptide B beta 15-42 were significantly raised in the plasma of patients with systemic lupus erythematosus and the anticoagulant compared with concentrations in patients without the lupus anticoagulant. The tendency towards formation of thrombosis was not found in all lupus patients with the anticoagulant, however. Concentrations of thromboxane B2 were remarkably raised in the plasma of the two patients with the lupus anticoagulant who had recently had thrombosis. Concentrations of 6-keto-prostaglandin F1 alpha, protein C, antithrombin III, and plasminogen were similar in both groups. No significant decrease in serum stimulatory activity on prostacyclin production by cultured aortic endothelial cells was noted in lupus patients with the anticoagulant, but inhibition was present in the two patients with recent thrombosis. These results indicate that although patients with the lupus anticoagulant are not always in a hypercoagulable state, haemostatic abnormalities found in some patients with the anticoagulant may be predictive of thrombotic events.